Application and Research Progress of Fat Substitutes in Meat Products Processing - Wantian XU; Yujuan XU; Cong LI; Hui ZHOU; Xiangjie MA; Baocai XU (Shipin gongye ke-ji)
Fat can provide the necessary energy for the body and play a role in improving the sensory quality during the processing of meat products, but excessive intake of fat may lead to obesity, cardiovascular disease and other health problems. With the improvement of people's food safety and health consciousness, low-fat meat products are sought after by consumers. In recent years, fat substitutes have become one of the current research hotspots for low-fat processing of meat products. Traditional fat substitutes such as dietary fiber, pre-emulsion, and protein matrix cannot completely simulate the taste of fat, which will lead to a decrease in the sensory quality of meat products. New fat substitutes such as oleogel and emulsion gel can better simulate the taste of animal fat by modifying fats and oils, but the acceptance of them is low. Currently, fat substitutes are mainly used in western meat products such as Frankfurter sausage and hamburger patties, and less research has been conducted in Chinese meat products. This paper predicts that research on fat substitutes will be carried out from the perspectives of research and development of new fat substitutes, addition of functional factors, and digestion and absorption of fat substitutes in the human body, with the aim of providing ideas and technical support for the improvement of the consumption quality of new fat-reduced meat products.